SIFO - an insufficiently researched, but clinically significant issue. What do we know so far? Can physical activity help to relieve gastrointestinal symptoms? - Magierska, Agata; Kwaśniak, Ksenia; Foryś, Angelika; Miłek, Magdalena; Banach, Mariola; Ślusarczyk, Monika; Stawska, Weronika; Niemczyk, Anna; Kmiotek, Weronika; Kotowicz, Zuzanna (Quality in Sport, 2024)
Introduction and purpose: Small intestinal fungal overgrowth (SIFO) presents as an excessive presence of fungi in the small intestine, often associated with gastrointestinal (GI) symptoms like unexplained gas, bloating, pain, malabsorption, and irregular bowel movements, including constipation or diarrhea. The study aims to organize information regarding this condition, emphasizing the lack of specific guidelines regarding diagnosis and treatment and need for treatment that are not only based on systemic drugs but also additional ways such as physical activity. Materials and methods: We conducted a literature review utilizing the medical databases PubMed and Google Scholar, retrieving articles in English using keywords such as "small intestinal fungal overgrowth," "SIFO," "gastrointestinal symptoms," "enterocolitis," " exercising," and "brain-gut axis" in various combinations. Our analysis included data from 33 scientific references published between 1931 and 2023. Summary: Small intestinal fungal overgrowth (SIFO) is more often acknowledged as a potential factor for unexplained gastrointestinal symptoms. More and more clinicians attach importance to this issue, as it is a serious clinical burden which significantly reduces quality of life. Nevertheless, the precise clinical impact of SIFO within the community remains uncertain as the available literature primarily consists of isolated case reports or observations from autopsies of patients undergoing cancer treatment. There still are no specific guidelines for diagnosis and treatment. Clinicians use systemic antifungal drugs. There is a potential in physical activity as an additional way to treat this condition.